Pelatihan Penyusunan Proposal Usaha Kepada Mahasiswa dalam Kegiatan Bursa Metamorfosa UKM Kewirausahaan Bursa FEB Unsoed - Fitri Amalinda Harahap; Ronald Haryanto (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2023)
One strategy that can be implemented to escalate a country's economy is maximizing entrepreneurship. This activity offers various types of products and services. The community members have the same opportunity to participate in these activities. The government also supports the community by implementing various kinds of workshops to increase the knowledge and skills of entrepreneurs in Indonesia. One of the potential entrepreneurs is the younger generation, which is students. To maximize this potency, UKM Kewirausahaan Bursa FEB UNSOED organizes an event called Bursa Metamorfosa to increase student passion for entrepreneurship by providing business experience. Bursa Metamorfosa consists series of activities with the goal is doing business incubation the earlier stage of this process is preparing a business proposal. Business proposals are an important key to running a business, especially if it requires investors to support its activities.